A process-depositional model for the evaluation of archaeological potential and survey methods in a boreal forest setting, Northeastern Alberta, Canada - Woywitka, Robin; Froese, Duane (My University, 2020)
More than 1,000 archaeological sites occur within the Clearwater-Athabasca Spillway, a relict channel that routed catastrophic drainage from glacial Lake Agassiz during deglaciation of northeastern Alberta. This high site density is rare in the region, and artifact assemblages are large due to the presence of abundant sources of lithic raw material. Unfortunately, sites are rarely preserved in stratified or deeply buried deposits. As is often the case in subarctic areas, this lack of depositional context coupled with a paucity of datable organic materials has hindered the establishment of cultural chronologies for the region. To address this issue, we develop a process-depositional model and digital terrain analysis to identify where thicker sediments may have accumulated, and assess whether survey strategies have adequately tested these areas. We find current survey strategies are biased to testing upland ridges with thin deposits, and that inconsistent methods of recording sediment thickness make it difficult to assess whether vertical profiles are being sampled to sterile deposits. We recommend that future survey strategies in boreal forest settings focus on a broader suite of landforms and landform elements, including those that act as sediment traps.
Keywords: archaeological modeling; boreal forest; eolian deposits; geoarchaeology; terrain analysis